Nekam's disease - Chintaginjala Aruna; D. V. S. B. Ramamurthy; T Neelima; Haritha Bandaru (Wolters Kluwer Medknow Publications, 2016)
Keratosis lichenoides chronica also known as Nekam's disease is a rare mucocutaneous disorder, characterized clinically by asymptomatic violaceous keratotic papules arranged in linear, reticular, or plaque form usually on the trunk and extremities and histologically by interface dermatitis. The disease is considered rare with only 128 cases being reported in the literature till date and very few from India. We report a case of a 40-year-old man who presented with constellation of features of lichen planus, seborrheic dermatitis, and apthous ulcers, which upon workup was found to be Nekam's disease.